Variations of Training Workload in Micro- and Meso-Cycles Based on Position in Elite Young Soccer Players: A Competition Season Study - Nobari, Hadi; Vahabidelshad, Reyhaneh; Pérez-Gómez, Jorge; Ardigò, Luca Paolo (Frontiers in Physiology, 2021)
The objectives of this study were to quantify the and matches training workload in micro-cycles of an elite young soccer team considering field position and to explain meso-cycles based on change of weekly acute (wAWL), chronic load (wCWL), acute to chronic workload ratio, training monotony (wTM) and training strain (wTS) between early-, mid- and end-season periods considering playing position and whole team. Twenty-six under-16 years’ elite young soccer players participated in this study including six wide defenders and wide midfielders (WM), five central defenders (CD) and central midfielders and four strikers (ST). Daily monitoring was performed by players for 20 weeks with the rating of perceived exertion using the Borg CR-10 scale. In comparison with early-season, result showed that there was a significant increase, in all playing position, in wAWL and wCWL (except ST) and in wTM (except CD and ST) compared with end-season. On the other hand, there were significant reductions in wTS in CD, WM and ST at the end-season. According to the results, coaches should consider the field position in different situations. Differences between training workload and matches can be a good guide for coaches, who have a special look at the object that have more load in training programs. Excessive training workload can typically potentially cause injury to adolescent athletes and controlling wTM can prevent this individually.